REKONSTRUKSI TEORI AGAMA PRIMITIF DI ERA POSTMODERNISME - Fitriani Fitriani (UIN Sumatera Utara Medan, 2023)
Every soul in the human person have great curiosity about a substance that created them or a substance that is believed to have power which can also be interpreted as a ruling spirit. Therefore, various views arose regarding what is called primitive belief or religion. The history of the emergence of primitive religion is increasingly being discussed by thinkers in modern to postmodern times because the emergence of religion often becomes a science used as research material by academics. Various theories were put forward as material for finding factual data related to the early emergence of primitive religion. The method used in this study is the library study method, the data obtained through books, journals or research related to the reconstruction of primitive religious theory. This study uses an anthropological approach to religion which seeks to understand religion by examining forms of religious practice that grow and develop in the life of primitive society. The results of the research reveal the reconstruction of primitive religious theories, various forms of primitive religion, theories that gave rise to primitive religious beliefs, and the characteristics of primitive religious adherents to the reconstruction of views on primitive religion. The result of this discussion is that the theory regarding the emergence of primitive religion put forward by Eastern scientists often encounters many disputes with the ideas of Western Orientalists. Most western orientalists assume that primitive religion emerged at the very beginning of human civilization itself, although there are several western theories which say that what is meant by primitive humans is a society far from civilization. This proves the importance of studying the reconstruction of primitive religious theory in the postmodern era.